KEDUDUKAN HUKUM KREDITUR TERHADAP OBJEK HAK TANGGUNGAN ATAS PEMBATALAN AKTA PEMBERIAN HAK TANGGUNGAN OLEH PENGADILAN AKIBAT TIDAK BERWENANGNYA PEMBERI HAK TANGGUNGAN (STUDI PUTUSAN MAHKAMAH AGUNG No. 1842 K/Pdt/2003) - MANUSUN NAINGGOLAN (PREMISE LAW JURNAL, 2016)
A banking credit contract has a degree of risk. In general, the Bank as a creditor will ask for a debtor's movable and immovable property to be used as collateral in the process of giving the credit in order to secure the credit channel from the risk of nonperforming loan or the debtor is not able to pay off his loan. The research used judicial normative and descriptive analytic. It is made by using authentic deed ofPPAT (official empowered to draw up land deeds) and was registered in the Land Office where the land was located so that it has legal enforcement and legal certainty in its implementation. The consideration of the panel of judges of the Supreme Court in their Ruling No. 1842 K/Pdt/2003 was that the debtor who gave the hypothecation had committed legal act because he had given collateral obtained illegally so that the APHT was cancelled by the Court since it was legally defective and contrary to the prevailing legal provisions on Hypothecation. Keywords : Position of Law on Creditor, Collateral, Cancelling APHT by the Court, Unauthorized Debtor